Differentiation of Lymph-Node Metastases by Anti-CEA Immunoscintigraphy in a Patient with Follicular Thyroid and Breast Cancer - Lind, P.; Lechner, P.; Kuttnig, M.; Klimpfinger, M.; Langsteger, W.; Költringer, P.; Cesnik, H.; Eber, O. (Nuklearmedizin - NuclearMedicine, 1990)
Supraclavicular lymph node metastases appeared in a female patient six years after thyroidectomy, radioiodine therapy and external radiation for a follicular thyroid carcinoma and four years after mastectomy and lymphadenectomy for an invasive ductal breast cancer. It was not possible either by conventional imaging methods or by serological methods, to assign the metastases to one of the two primary tumors. Anti-CEA immunoscintigraphy and SPECT of the cervicothoracic region showed a circumscribed pathological uptake of 99mTc-labeled anti-CEA antibodies in the area of the supraclavicular lymph nodes. The preoperative suspicion of lymph-node infiltration by CEA-expressing breast cancer cells was confirmed histologically after surgical removal of the lymph nodes.Sechs Jahre nach Strumektomie, Mega-Radiojodtherapie und externer Bestrahlung wegen eines follikulären Schilddrüsenkarzinoms sowie 4 Jahre nach Mastektomie und Lymphadenektomie wegen eines invasiv duktalen Mammakarzinoms traten bei einer weiblichen Patientin supraklavikuläre Lymphknotenmetastasen auf. Weder mit den konventionellen bildgebenden Verfahren noch mit serologischen Methoden konnte eine Zuordnung der Metastasen zu einem der beiden Primärtumore erreicht werden. Die Anti-CEA-Immunszintigraphie und SPECT der Zervikothorakalregion zeigte eine umschrieben pathologische Anreicherung 99mTc-markierter monoklonaler anti-CEA-Antikörper im Bereich der supraklavikulären Lymphknoten. Die bereits präoperativ vermutete Infiltration der Lymphknoten durch CEA-exprimierende Mammakarzinom-Zellen wurde nach operativer Entfernung der Lymphknoten histologisch bestätigt.